The Ambiguous Authority of Provincial Governors in Customary Law Recognition: Regulatory Fragmentation in Indonesia’s Decentralization Era - Rizki Jayuska; I Gusti Ayu Ketut Rachmi Handayani; Isharyanto Isharyanto; Ismail Marzuki; Achmad Fawaid (UIN Sunan Gunung Djati, 2025)
This study aims to analyze the structural, institutional, and regulatory challenges in recognizing Indigenous Law Communities (Masyarakat Hukum Adat/MHA) in Indonesia, with a particular focus on the strategic yet ambiguous role of provincial governments. Despite the legal mandate for decentralization, the dual function of governors as regional heads and central government representatives has not been supported by a clear legal framework to facilitate cross-district recognition of MHA. Using a qualitative approach, the study employs document analysis of legal texts, regional regulations, and case studies, supported by secondary data from institutional reports and scholarly publications. The findings reveal three major issues: first, the absence of a legal mandate for governors to coordinate inter-district recognition processes; second, regulatory conflicts between provincial and district-level authorities, especially when indigenous territories cross administrative boundaries; and thrid the lack of harmonization between regional customary regulations and national laws. These obstacles have resulted in legal uncertainty, fragmented policy implementation, and continued marginalization of indigenous communities. This research contributes to the discourse on multilevel governance by emphasizing the overlooked role of governors in indigenous rights recognition. It also identifies practical entry points for policy reform, such as enhancing judicial review mechanisms, formalizing adat institutions, and improving spatial data integration across ministries. The originality of this study lies in shifting the analytical lens from district-level actors to the provincial level, proposing a coordinated, vertically and horizontally integrated governance framework for sustainable recognition of indigenous communities in Indonesia.